2024
DOI: 10.1111/ijfs.17097
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Salmonella in poultry meat and products in Türkiye: Prevalence, antibiotic susceptibility and genomic characterisation

Adalet Dishan,
Harun Hizlisoy,
Nurhan Ertaş Onmaz
et al.

Abstract: SummaryThe study aimed to determine the prevalence and characteristics of Salmonella isolated from raw chicken meat and products. For this purpose, a total of 293 samples were collected, including chicken breast (n = 90), skinned drumstick (n = 80), skinned chicken chop (n = 42), wing (n = 32), chicken offal (n = 27) and chicken patty (n = 22). The samples were subjected to Salmonella enterica. detection and the obtained suspicious isolates were confirmed by conventional PCR. Their phenotypical antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
0
0
Order By: Relevance
“…The Salmonella isolates (36/48) in this study were further screened for the presence of S. Enteritidis and S. Typhimurium, where eight (22.2%) isolates were confirmed as S. Enteritidis, while 14 (38.9%) were S. Typhimurium. A comparative study conducted in Egypt reported a low prevalence of S. Typhimurium (3%) and S. Enteritidis (2%) serovars in chicken meat [32]. Another study conducted in Egypt recorded a low prevalence of S. Enteritidis (9%), while the same study recorded high prevalence of S. Typhimurium (86.6%) in chickens [23].…”
Section: Discussionmentioning
confidence: 93%
“…The Salmonella isolates (36/48) in this study were further screened for the presence of S. Enteritidis and S. Typhimurium, where eight (22.2%) isolates were confirmed as S. Enteritidis, while 14 (38.9%) were S. Typhimurium. A comparative study conducted in Egypt reported a low prevalence of S. Typhimurium (3%) and S. Enteritidis (2%) serovars in chicken meat [32]. Another study conducted in Egypt recorded a low prevalence of S. Enteritidis (9%), while the same study recorded high prevalence of S. Typhimurium (86.6%) in chickens [23].…”
Section: Discussionmentioning
confidence: 93%